The applied study to improve the treatment of knee sports injuries in ultimate frisbee players based on personalized exercise prescription: a randomized controlled trial - Chen, Shangmin; Du, Lin; Gao, Yongshan; Li, Haorui; Zheng, Yanxun; Xie, Lei; Zhong, Zhigang (Frontiers in Public Health, 2024)
Objective Ultimate frisbee can lead to severe sports injuries, especially joint injuries in the lower limbs, such as knee meniscus injuries. This study examines the impact of personalized exercise therapy on knee meniscus injuries in ultimate frisbee players in the Lingnan region of China. Methods Seventy-six patients with confirmed meniscal injuries participated in the study, divided into an intervention group (n = 38) and a control group (n = 38). The control group received standard treatment, including drug therapy and physical therapy. The intervention group received standard treatment plus a personalized exercise regimen based on FITT-VP (frequency, intensity, time, type, volume, and progression) principles, incorporating strength training, aerobic exercise, flexibility training, neuromuscular training, and aquatic exercise. This program was monitored and adjusted over a six-month period through both online and offline methods. The primary outcomes were joint range of motion (ROM), thigh circumference atrophy index (TCAI), Lysholm Rating Scale (LRS) scores, and visual analog scores (VAS). The secondary outcome was the International Knee Documentation Committee (IKDC) score. Data were collected before the intervention, and at 1 month and 6 months after the intervention. Statistical analysis was conducted using SPSS 24.0 and GraphPad 10.0, with a significance level set at α = 0.05. Results After 1 month, the intervention group showed significantly better results in ROM (116.67 ± 9.063), LRS score (86.316 ± 3.750), and IKDC score (80.473 ± 5.421) compared to the control group (111.784 ± 4.778, 82.579 ± 3.818, and 77.684 ± 4.430, respectively) (p < 0.05). The TCAI (3.219 ± 1.889) and VAS score (1.921 ± 0.673) in the intervention group were significantly lower than those in the control group (5.228 ± 2.131 and 2.710 ± 1.112, respectively) (p < 0.01). After 6 months, the differences in LRS and VAS scores between the groups were not significant. However, the intervention group continued to show significant improvements in ROM (134.934 ± 3.011), TCAI (1.107 ± 1.158), and IKDC score (93.315 ± 1.847) compared to the control group (125.395 ± 18.554, 4.574 ± 1.109, and 87.789 ± 4.437, respectively) (p < 0.05). Conclusion Personalized exercise prescriptions offer significant therapeutic and rehabilitative benefits for ultimate frisbee players with knee meniscus injuries. This approach helps to reduce symptoms, alleviate pain, and improve joint function, muscle strength, and athletic performance after sports-related injuries.